2017
DOI: 10.3389/fimmu.2017.00317
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Dependent Cell-Mediated Cytotoxicity Epitopes on the Hemagglutinin Head Region of Pandemic H1N1 Influenza Virus Play Detrimental Roles in H1N1-Infected Mice

Abstract: Engaging the antibody-dependent cell-mediated cytotoxicity (ADCC) for killing of virus-infected cells and secretion of antiviral cytokines and chemokines was incorporated as one of the important features in the design of universal influenza vaccines. However, investigation of the ADCC epitopes on the highly immunogenic influenza hemagglutinin (HA) head region has been rarely reported. In this study, we determined the ADCC and antiviral activities of two putative ADCC epitopes, designated E1 and E2, on the HA h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…[48][49][50] For influenza, the role of ADCC was shown to be protective in some studies, 51,52 but others point to the involvement of ADCC in exaggeration of the immune response. [53][54][55] Taken together, these examples show that the capacity of pathogenspecific antibodies to engage NK cells can significantly contribute to the outcome of infection. Regarding RSV infection, in mice, NK cells have been shown to be sufficient to eliminate infection 56 and NK cell depletion was found to increase viral titres.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[48][49][50] For influenza, the role of ADCC was shown to be protective in some studies, 51,52 but others point to the involvement of ADCC in exaggeration of the immune response. [53][54][55] Taken together, these examples show that the capacity of pathogenspecific antibodies to engage NK cells can significantly contribute to the outcome of infection. Regarding RSV infection, in mice, NK cells have been shown to be sufficient to eliminate infection 56 and NK cell depletion was found to increase viral titres.…”
Section: Discussionmentioning
confidence: 89%
“…For HIV, ADCC‐inducing antibodies have been identified as a key correlate of protection in the RV144 HIV vaccine trial . For influenza, the role of ADCC was shown to be protective in some studies, but others point to the involvement of ADCC in exaggeration of the immune response . Taken together, these examples show that the capacity of pathogen‐specific antibodies to engage NK cells can significantly contribute to the outcome of infection.…”
Section: Discussionmentioning
confidence: 98%
“…For HIV, ADCC-inducing antibodies have been identified as a key correlate of protection in the RV144 HIV vaccine trial (44-46). For influenza, the role of ADCC was shown to be protective in some studies (47, 48), but others point to the involvement of ADCC in exaggeration of the immune response (49-51). Taken together, these examples show that the capacity of pathogen-specific antibodies to engage NK cells can significantly contribute to the outcome of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry-based ADCC assays are developed to measure ADCC activity by using different fluorescent dyes to differentiate living and dead cells [70,71]. In this assay, PKH-67 is used to label both live and dead target cells while dead target cells and effector cells are labeled with 7-amino actinomycin D (7-AAD).…”
Section: Target Cell Killing Assaymentioning
confidence: 99%
“…The antigen needs to be carefully designed and inclusion of an adjuvant is also critical to protective outcome. Four, there are reports of antibody-dependent enhancement (ADE) in ADCC-mediating antibodies [71,133]. In these studies, ADCC epitopes were identified and these epitope-based vaccines were generated and tested in mice.…”
Section: Adcc-based Vaccinementioning
confidence: 99%